Nocitainment: the contemporary construction of pain as amusement. Issue 4 (December 2016) - van Ommen, Clifford
Abstract In this article, I explore the management and construction of physical pain in video-clip-based television programmes, as well as the sociopolitical context in which these are embedded, and the form of subjectivity simultaneously celebrated and evoked. The analysis focuses on the popular MTV television series, Ridiculousness, in which internet video clips are commented on by the hosts for comedic effect. Many of these clips depict physical pain, usually as a consequence of a person having an accident. Drawing on Scarry'sThe Body in Pain (1985), I show how a particular set of strategies are utilised and constructions are legitimated for the experience and interpretation of pain. These techniques not only bear a striking resemblance to the structure of torture but are also conservative in their effect as they promote neoliberal processes of subjectification and reiterate a particular form of masculinity.